MOLECULAR PROFILING AND ANTIMICROBIAL RESISTANCE PATTERNS OF EXTENDED-SPECTRUM BETA-LACTAMASE-PRODUCING ESCHERICHIA COLI ISOLATES FROM CLINICAL SAMPLES IN SOUTHWESTERN NIGERIA - Akindele, Abiodun A.; Aro, Elizabeth O.; Ojedele, Richard O.; Odewale, Gbolabo; Bolaji, Oloyede S. (FUDMA JOURNAL OF SCIENCES, 2025)
Introduction: Escherichia coli (E. coli) is a Gram-negative that can become true pathogenic. Extended-spectrum Beta-lactamases (ESBLs) are enzymes that make bacteria resistant to antibiotics, posing risks for infections and requiring strict infection control measures. Methodology: A hospital-based study in Southwestern Nigeria (August–November 2020) analyzed 105 Escherichia coli isolates using biochemical tests, EMB agar, and PCR for molecular identification. Antibiotic susceptibility was assessed via the Kirby-Bauer method, interpreted using CLSI criteria. Molecular analysis identified blaCTX, blaSHV, and blaTEM genes. Data underwent descriptive analysis and Chi-square testing, with a p-value <0.05 considered significant, highlighting associations between variables and antibiotic resistance genes. Results: It was discovered that 35 out of 105 (33.3%) clinical Escherichia coli isolates were confirmed to be Escherichia coli isolates using the TEcol primer. At least one of the three (3) genes of ESBL was screened for in 60% of the confirmed Escherichia coli isolates; 17.1%, 37.1% and 40% of the isolates had SHV, TEMH and CTX-M genes respectively. There was 100% resistivity of the extended-spectrum beta-lactamases producing Escherichia coli isolates to Amoxycillin/Clavulanic acid, Meropenem, Oxacillin, Ceftazidime and Cefepime; 33.3%, 47.6%, 61.9%, 71.4% and 81% of the extended-spectrum beta-lactamases-producing isolates were resistant to Imipenem, Chloramphenicol, Levofloxacin, Ciprofloxacin and Cefoxitin respectively. Significance of Results: There is prevalence of blaCTX-M-positive extended-spectrum beta-lactamases isolates, and increasing spread of extended-spectrum beta-lactamases-producing clinical Escherichia coli isolates in Southwest Nigeria. Conclusion: There is existence and increasing production of Extended-spectrum Beta-lactamases in some clinical isolates of Escherichia coli.